MAS-1, a novel water-in-oil adjuvant/delivery system, with reduced seasonal influenza vaccine hemagglutinin dose may enhance potency, durability and cross-reactivity of antibody responses in the elderly - Gorse, Geoffrey J.; Grimes, Stephen; Buck, Helen; Mulla, Hussain; White, Peter; Hill, Heather; May, Jeanine; Frey, Sharon E.; Blackburn, Peter (Vaccine, 2022)
•MAS-1 adjuvant with 9 µg per hemagglutinin in 0.3 mL was safe and immunogenic in the elderly.•Antibodies to adjuvanted vaccine peaked by 85 days and were durable at 169 days.•Responses to adjuvanted vaccine appeared better than high dose influenza vaccine.•Adjuvanted vaccine induced seroresponses to non-study vaccine strains.•Late injection site reactions occurred with adjuvanted vaccine 0.5 mL dose volume. Increased influenza vaccine efficacy is needed in the elderly at high-risk for morbidity and mortality due to influenza infection. Adjuvants may allow hemagglutinin (HA) dose-sparing with enhanced immunogenicity. MAS-1 is an investigational water-in-oil emulsion-based adjuvant/delivery system comprised of stable nanoglobular aqueous droplets. A phase 1, randomized, double-blind, safety and immunogenicity, adjuvant dose escalation trial was conducted in persons aged 65 years and older. MAS-1 adjuvant dose volumes at 0.3 mL or 0.5 mL containing 9 µg per HA derived from licensed seasonal trivalent influenza vaccine (IIV, Fluzone HD 60 µg per HA, Sanofi Pasteur) were compared to high dose (HD) IIV (Fluzone HD). Safety was measured by reactogenicity, adverse events, and safety laboratory measures. Immunogenicity was assessed by serum hemagglutination inhibition (HAI) antibody titers. Forty-five subjects, aged 65–83 years, were randomly assigned to receive 9 µg per HA in 0.3 mL MAS-1 (15 subjects) or HD IIV (15 subjects) followed by groups randomly assigned to receive 9 µg per HA in 0.5 mL MAS-1 (10 subjects) or HD IIV (5 subjects). Injection site tenderness, induration, and pain, and headache, myalgia, malaise and fatigue were common, resolving before day 14 post-vaccination. Clinically significant late-onset injection site reactions occurred in four of ten subjects at the 0.5 mL adjuvant dose. Safety laboratory measures were within acceptable limits. MAS-1-adjuvanted IIV enhanced mean antibody titers, mean-fold increases in antibody titer, and seroconversion rates against vaccine strains for at least 168 days post-vaccination and enhanced cross-reactive antibodies against some non-study vaccine influenza viruses. MAS-1 adjuvant provided HA dose-sparing without safety concerns at the 0.3 mL dose, but the 0.5 mL dose caused late injection site reactions. MAS-1-adjuvanted IIV induced higher HAI antibody responses with prolonged durability including against historical strains, thereby providing greater potential vaccine efficacy in the elderly throughout an influenza season. Clinical Trial Registry: ClinicalTrials.gov # NCT02500680.